5х+(13,4-2х)=16,4х 5(2х-3)+11=6х
3х+13,4-16,4х=0 10х-15+11-6х=0
-13,4х+13,4=0 10х-4-6х=0
4х-4=0
12-(4х+5)=7+х
12-4х-5-7-х=0 1,7х+0,9=2х
7-4х-7-х=0 -0,3х+0,9=0
-4х-х=0
-5х=0 -2(7-у)+13=у
-(14-2у)+13-у=0
-14+2у+13-у=0
-1+2у-у=0
-1+у=0
2х+1/3-х-2у/5=4(2х+у)/15
х-4у/3+5х-11у/6=3х-1/4
упростим для начала
2х+1/3-х-2у/5=4(2х+у)/15
х-4у/3+5х-11у/6=3х-1/4
х+1/3-2у/5=8х/15+4у/15
6х-8у/6-11у/6=3х-1/4
15х/15-6у/15-8х/15-4у/15=-1/3
6х-3х-19у/6=-1/4
7х/15-10у/15=-5/15
3х-19у/6=-1/4
выразим из первого уравнения х и подставим во второе
7х/15=10у/15-5/15
7х=10у-5
х=(10у-5)/7
3*(10у-5)/7-19у/6=-1/4
30у/7-15/7-19у/6=-1/4 приведем к общ знаменателю 84
30*12*у-19*14*у=15*12-1*21
360у-266у=180-21
94у=159
у=159/94=1целая 65/94
х=(159*10/94-5)/7=(795/47-235/47)/7=560/(47*7)=80/47= 1 целая 33/47
получается:
104:26=4
ответ: в 4 раза